Earnings Management in the Pre and Post eXtensible Business Reporting Language Period in Indonesia - Arung Gihna Mayapada; Muhammad Afdhal; Rahmi Syafitri (The Indonesian Journal of Accounting Research, 2020)
This study aims to determine and analyze the impact of XBRL adoption on earnings management conducted by company management in Indonesia. Earnings management in this study is proxied by discretionary accruals. The population of this research is manufacturing companies listed on the Indonesia Stock Exchange. The research sample was selected using the purposive sampling method. The total sample of this research is 15 manufacturing companies. This research period includes the period before the adoption of XBRL (2012-2014) and the period after the adoption of XBRL (2015-2017). Hypothesis testing is done by a paired sample t-test. The results of hypothesis testing indicate that there are significant differences between the levels of earnings management in the period before and after the adoption of XBRL. These results reveal that the adoption of XBRL can limit the opportunistic behavior of management in presenting financial reporting. These results also reveal that the adoption of XBRL can improve the quality of financial reporting.